Implementasi Sistem Monitoring Pertumbuhan Tanaman Hidroponik Berbasis Sensor Konduktivitas dan LabVIEW - Nuralam, Nuralam; Muzakki, Rizdam Firly; Kusumastuti, Sri Lestari; Hariyanto, Hariyanto (Jurnal Kridatama Sains dan Teknologi, 2025)
This community service project is an implementation of research findings. Hydroponic farming offers an innovative solution to land scarcity and soil degradation in urban areas. Its success heavily depends on the management of nutrient solution quality, particularly in terms of electrical conductivity (EC) and temperature. In the local hydroponic farm, residents were still using manual methods that are inaccurate and lack data logging capabilities. Therefore, an EC and temperature sensor-based monitoring system integrated with LabVIEW was developed. The system is designed to provide real-time readings, color-coded visual indicators, and automatic data logging. Testing was conducted over six days at a lettuce hydroponic installation, yielding an average EC deviation of 3.2% compared to a reference device. The measured temperature range remained within the ideal range (26.1–28.3°C). The system operated stably with a 1-second reading interval, low power consumption, and compatibility with local conditions. Positive user feedback highlighted its ease of use and practical benefits in plant maintenance decision-making. Through this appropriate technology approach, the system has the potential to serve as a model for smart household-scale agricultural development in urban areas